Respuesta :

Answer:

Option (B)

Step-by-step explanation:

If A = [tex]\begin{bmatrix}1 & 3\\ -2 & 5\end{bmatrix}[/tex] and B = [tex]\begin{bmatrix}-2 & 1\\ 3 & 4\end{bmatrix}[/tex]

Multiplication of these matrices,

A.B = [tex]\begin{bmatrix}1 & 3\\ -2 & 5\end{bmatrix}\times \begin{bmatrix}-2 & 1\\ 3 & 4\end{bmatrix}[/tex]

      = [tex]\begin{bmatrix}(1(-2)+3(3) & 1(1)+3(4)\\ (-2)(-2)+5(3) & 1(-2)+5(4)\end{bmatrix}[/tex]

      = [tex]\begin{bmatrix}7 & 13\\ 19 & 18\end{bmatrix}[/tex]

Therefore, Option (B) will be the answer.

ACCESS MORE